1988
DOI: 10.1182/blood.v71.2.388.bloodjournal712388
|View full text |Cite
|
Sign up to set email alerts
|

Factor V is activated and cleaved by platelet calpain: comparison with thrombin proteolysis

Abstract: Platelets are known to process human factor V during secretion and/or membrane binding. We studied the functional and structural changes produced in human factor V by purified human platelet calpain (calcium- activated thiol protease) and compared the alterations with those induced by thrombin. A maximum increase in coagulant activity of 2.5- fold was observed when factor V (1 U/mL, 33 nmol/L) was incubated with calpain (0.03 U/mL, 2.7 nmol/L) in comparison with a 8.8-fold increment for alpha-thrombin (0.7 U/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…After these studies, most approaches aimed at understanding how FV is activated were principally based on correlating bond cleavage within the B‐domain with the development of procoagulant activity. These studies have largely relied on the kinetic appearance of proteolytic fragments during activation [77,79,82,83,98,99], reconstituted FV activation products [82,85], FV(a) derivatives generated by a variety of proteases [77,99–111] and recombinant FV derivatives with specific modifications to thrombin cleavage sites to establish this correlation [94,112–115]. While somewhat conflicting results have emerged, most data support the idea that variable amounts of cofactor activity will be observed depending on which region of the B‐domain is cleaved and which assay is employed to evaluate activity.…”
Section: Fv Procofactor Activation: Transition To the Active Cofactormentioning
confidence: 99%
“…After these studies, most approaches aimed at understanding how FV is activated were principally based on correlating bond cleavage within the B‐domain with the development of procoagulant activity. These studies have largely relied on the kinetic appearance of proteolytic fragments during activation [77,79,82,83,98,99], reconstituted FV activation products [82,85], FV(a) derivatives generated by a variety of proteases [77,99–111] and recombinant FV derivatives with specific modifications to thrombin cleavage sites to establish this correlation [94,112–115]. While somewhat conflicting results have emerged, most data support the idea that variable amounts of cofactor activity will be observed depending on which region of the B‐domain is cleaved and which assay is employed to evaluate activity.…”
Section: Fv Procofactor Activation: Transition To the Active Cofactormentioning
confidence: 99%
“…Platelet proteases may also cleave and activate FV (17)(18)(19). Bradford et al (20) documented the potential for activation of human plasma FV by calpain, a major platelet protease, and indicated that the cleavage products differed from those produced by thrombin. Platelet FV has been isolated and characterized as a partially fragmented procofactor (21).…”
Section: Introductionmentioning
confidence: 99%
“…However, several other observations are inconsistent with a role for calpain in proteolysis of FV following megakaryocyte endocytosis. In contrast to megakaryocyte‐derived FV or FV/Va stored in platelets, fragments similar in size to the bonafide FVa heavy chain and light chain were not observed . Moreover, while previous observations have demonstrated that platelet calpain cleaves fibrinogen , it remains intact subsequent to its endocytosis by megakaryocytes (see Fig.…”
Section: Discussionmentioning
confidence: 72%
“…m‐ and mu‐Calpains, abundant in many cell types , are calcium‐dependent cysteine proteases that also cleave their substrates at tyrosine residues . Calpain purified from platelets cleaves plasma‐derived FV rapidly to produce several polypeptides including fragments expressing a limited amount of cofactor activity . Many of these polypeptides were similar in size to those derived from megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%